Ecomorfologia predizendo a segregação do nicho trófico entre dois Ciclídeos neotropicais. - Sampaio, Ana Lúcia Antunes (2011)
Considering the morphology and diet of Satanoperca pappaterra and Crenicichla britskii (Perciformes: Cichlidae) in the upper Paraná River floodplain the aim of this study was to verify the morphological segregation and the pattern of resources use among these species. We tested the hypothesis in which morphology is closely related to the use of food resources, assuming that morphological differences imply different forms of exploitation of resources and the ecomorphological analysis allows the identification of patterns of segregation of trophic niche. Five samplings were carried out along different habitats of the Upper Paraná River floodplain (22º40'S 53º15'W e 22º50'S 53º40'W). We analized the stomach contents of 70 individuals of S. pappaterra and 17 of C. britskii and the main morphological structures related to feeding were characterized. Concomitantly, 22 ecomorphological indices were calculated from linear morphometric measurements and areas. Multivariate analysis and a correlation test were used to test the pre-supposed hypothesis. Principal component analysis revealed that S. pappaterra and C. britskii presented different morphological patterns, indicating that both species have adaptations for the exploitation of specific resources. It was observed that the morphological structures related to feeding were also suitable for exploitation of food resources. The diet showed significant differences between both species: S. pappaterra was characterized as detritivore, while C. britskii as piscivore. The Mantel test showed that the diet was significantly correlated with the body form. Therefore, the hypothesis that the morphology is closely related to the use of food resources was confirmed. Ecomorphological analysis allowed the visualization of trophic niche segregation between those species. Thus, the ecomorphology represents an effective tool to contribute with the understanding of how species respond to environmental pressures.